The Crypto Tax Shift: Analyzing Financial and Compliance Impacts on a Public Indonesian Exchange - Muhammad Nurdin; Hari Budi Utomo (STMIK Indonesia Banda Aceh, 2026)
This study investigates the impact of Indonesia's latest crypto asset tax regulations, specifically the significant shift outlined in PMK 50/2025 and PMK 108/2025, on the financial performance and compliance disclosure of publicly listed crypto companies, with a specific case study on PT Indokripto Koin Semesta Tbk. Two primary policies are examined: PMK 50/2025, which establishes a 0% Value Added Tax (VAT) on crypto asset transfers and a final income tax of 0.21% on transaction value, and PMK 108/2025, which mandates automatic reporting based on the Common Reporting Standard (CRS) and the Crypto-Asset Reporting Framework (CARF). The methodology integrates an event study and content analysis of interim financial reports for the first semester of 2025, alongside projections for the period after August 2025. Findings suggest that the removal of VAT has the potential to boost transaction volume, while the application of a final tax based on gross turnover may compress net margins. Furthermore, the adoption of CRS/CARF is projected to elevate information technology compliance costs and enhance the quality of disclosures within financial statements. These outcomes offer important implications for regulators, issuing companies, and investors navigating regulatory changes within the digital asset industry.